KONSEP DANA BANTUAN BAITUL MAAL PADA PEMBIAYAAN USAHA KECIL (Studi Kasus Di Baitul Maal Kota Sabang) - Fiddini Fiddini; Irwandi Irwandi (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
Baitul Maal was the first financial institution that existed at the time of the Prophet. At first, this institution only functioned to store state assets from zakat, infaq, alms, taxes and spoils of war. Baitul Maal Sabang City has several programs, including the Business Capital Assistance Fund program for Micro businesses, Muallaf coaching, Scholarships for Orphans and the Poor, Home Renovation, and work equipment assistance for poor families. business capital for economic traders down, with the concept of these funds borrowed and returned within a predetermined period. What is the position of Maal Aid funds in Small Business Financing, What is the Role of Baitul Maal in Small Business Financing in Sabang, What are the Obstacles and Barriers in Providing Business Capital Assistance in Small Business Financing. To find out and explain the position of Maal Aid funds in Small Business Financing, To find out and explain the role of Baitul Maal in Small Business Financing in Sabang, To know and explain the obstacles and obstacles experienced by the Baitul Maal and the Small Business Party. In writing this thesis, the author uses the method of field research (field research), namely research that is carried out directly in order to obtain data that is closely related to research by interviewing respondents and informants. The concept of Baitul Maal Assistance Fund for Small Business Financing in Sabang. The position of Fund Assistance on Small Business Financing at Baitul Maal City of Sabang is Assistance in the form of cash with the money system being returned to Baitul Maal City of Sabang by being deposited every month for a year. Without interest or other guarantees, the role of the Baitul Maal of Sabang City in Financing Small Business by way of collecting data on the number of poor Mustahik, both in terms of data obtained from each gampong and the number of aid proposals that go to Baitul Maal Sabang, then a survey is carried out by field officers to ensure the accuracy of the data. Constraints and obstacles to Baitul Maal in Sabang City in Financing are the distribution system and budget disbursement must wait for the budget to be approved, then many business aid proposals enter so that it is difficult to select them, then many beneficiaries do not return the money given by Baitul Maal. So it is difficult to give to others for the following year. Keywords: Aid Fund, Baitul Maal and Financing